(untitled) (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study was to compare the health-related quality of life between subjects in good health and subjects with breast cancer. Method/Statistical Analysis: A secondary analysis was performed with data from 255 adults using raw data from the Korean National Examination Survey (KNHANES) conducted from 2010 to 2017. Findings: Subjects with breast cancer displayed a poor level of health awareness and high activity confinement. The EQ-5D index scores between subjects in good health and subjects with breast cancer did not show any significant differences. However, factors affecting health related quality of life for subjects with breast cancer and subjects in good health were different. Household income, perceived health status and activity confinement were the strongest factors affecting the health related quality of life among subjects with breast cancer while residential area, level of education, household composition, perceived health status, activity confinement and BMI were significant for subjects in good health. Improvements/Applications: The results of the study will be instrumental in giving insights on health-related quality of life for patients with breast cancer and establishing nursing strategies to promote their HR-QoL.